Proteínas do plasma seminal e das células espermáticas de touros Bos indicus das raças brahman e guzerá associadas com os parâmetros seminais - Rêgo, João Paulo Arcelino do (2014)
The aim of this work was to study seminal plasma and whole sperm proteins and their association with sperm morphology and methods of semen collection and cryopreservation in Bos indicus bulls using a proteomics approach . Seminal plasma proteins were separated by two-dimensional electrophoresis or diferential gel electrophoresis and identified by mass spectrometry gel. Firstly, we described the seminal plasma proteome of Bos indicus bulls, identified the Binder of Sperm Proteins as the more abundant proteins in seminal fluid, while the spermadhesins formed the second group with higher expression. Positive and negative associations were found between seminal plasma proteins and the percentage of morphologically normal spermatozoa constituing possible molecular markers of this characteristic. In other hand, differences were identified in ejaculate volume and seminal plasma protein profile of Bos indicus bulls subjected to different methods of semen collection (internal artificial vagina and electroejaculation). Based on the analysis of two-dimensional gels, 22 spots had larger volumes in samples collected by internal artificial vagina, corresponding to 21 proteins. In contrast, 33 spots had larger volumes of samples collected by electroejaculation corresponding to 26 differents proteins. The proteins with great volume in samples obtained by internal artificial vagina and electroejaculation had epididymal and accessory sex glands origin, respectively. In the present study, others associations have been made among protein expression in seminal plasma and sperm cells and semen parameters after cryopreservation in Bos indicus bulls. The animals had not differences between body weight, scrotal circumference and seminal parameters pre-freezing. After cryopreservation, the semen parameters were analyzed by computer system (CASA) and the animals were divided into groups of low and high freezability. In the high freezability group were more expressed three proteins of seminal plasma and five proteins of sperm. For the group of low freezability were more expressed six different seminal plasma proteins. Regression models adopted for the intensities of the spots in the seminal plasma and sperm cells, as well as analysis of protein-protein interactions, indicate that most of the proteins inversely associated with post -thaw sperm viability may be expressed as a response to an oxidative stress and/or microbial attack before the semen cryopreservation of animals with low freezability. These parameters could not be detected by conventional sperm analysis. This results obtened by applying of the proteomics approach, could serve as guideline for future researchs aimed to identifed molecular markers of reproductive processes based on the expression of proteins in seminal plasma and sperm cells of Bos indicus bulls.